PENGALIHAN HAK MILIK ATAS PROPERTI ASING DALAM PERJANJIAN BERNAMA BERDASARKAN PERATURAN PEMERINTAH NO 103 TAHUN 2015 TENTANG KEPEMILIKAN RUMAH TEMPAT TINGGAL/HUNIAN BAGI ORANG ASING - Tsara Zahrina, - (2019)
The validity of ownership rights over land owned by Indonesian citizens by foreign citizens (foreigners) carried out by a notary with a notary deed / formal juridical land deed official does not violate the rules. However, the ownership of land rights by foreign citizens (WNA) materially cannot be protected by law, because the provision violates the provisions of Article 26 paragraph (2) of the UUPA because it is an indirect attempt to transfer ownership rights to land from Indonesian citizens ( Indonesian citizen) to foreigners (foreigners). Then, regarding the legal consequences of the deed of ownership rights to land owned by Indonesian citizens (WNI) by foreign citizens (WNA), by using a nominee agreement, made by a Notary / Acting Land Actor is null and void, so it cannot accountable for the use of land rights, because the nominee agreement does not meet the requirements of the agreement as determined by Article 1320 KUH - Civil. Thus, the parties, both Indonesian citizens and foreigners who entered into these agreements to give birth to a legal agreement, are null and void. Thus from the beginning the agreement was never born and there was never an agreement. Nominee agreements are an attempt to give the possibility for foreign nationals to have ownership rights over land that is prohibited by the LoGA by using a guise of buying and selling on behalf of Indonesian Citizens, so that the formal jurisdiction does not violate regulations. The country of Indonesia as a Nominee is legal smuggling. The legal smuggling still occurs, as a result the validity of the nominee agreement is questioned, and the position of the land due to the nominee agreement becomes unclear